Clinical significance of serum neuron-specific enolase in gastric adenocarcinoma. Issue 16 (April 2020) - Luo, Hai; Shen, Kexin; Sun, Hongyan; Li, Ruiqi; Wang, Zeming; Xie, Zhongshi
Abstract : Abstract: As a biomarker, neuron-specific enolase (NSE) has been widely recognized in the diagnosis of benign diseases and malignant tumors. This study aimed to investigate the potential diagnostic value of NSE in patients with gastric adenocarcinoma. Serum levels of the NSE were compared between 219 patients with gastric adenocarcinoma and 298 healthy individuals, NSE and clinicopathological parameters were analyzed. Meanwhile, to evaluate the diagnostic capability of NSE, the receiver operating characteristic (ROC), and area under curve (AUC) was calculated. In the present study, the median serum NSE level of the patient group was 20.770 ng/mL, which was higher than that of the control group 15.625 ng/mL ( P  < .05). Serum NSE level in patients group compared with healthy control was statistically significant ( P  < .05). Serum NSE level was associated with pathological tumor-node-metastasis (pTNM) staging, lymph node metastasis, and distant metastasis in patients with gastric adenocarcinoma. Besides, the AUC of NSE in gastric adenocarcinoma was 0.742, which was higher than those of the other 3 markers (0.573–0.644). Besides, the AUC of the combined 4 markers was higher than any individual marker (0.778). Serum NSE detecting may have good value for diagnosis of gastric adenocarcinoma. Besides, the combination of NSE, CEA, CA19–9, and CA242 performed even better than any single marker. Thus, the combined detection of the 4 tumor markers may be more useful for the diagnosis of gastric adenocarcinoma.